2004
DOI: 10.1364/ao.43.001752
|View full text |Cite
|
Sign up to set email alerts
|

Self-compensating fiber optic flow sensor system and its field applications

Abstract: A self-compensating fiber optic flow sensor system based on the principle of broadband white-light interferometers and cantilever beam bending is described. The fiber optic sensor system uses two fiber ferrule sensors that are bonded on either side of a cantilever beam to measure the flow rate by monitoring the air-gap changes caused by the bending of the cantilever beam. Cross sensitivity of the temperature and pressure dependence of the sensor can be compensated for automatically. The prototype sensor system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…One study has shown that white light interferometry-based methods are capable of measuring flow rate [83]. Here, the self-compensation fibre-optic sensor employed the principles of cantilever beam mechanics.…”
Section: Measurement Of Flow Parametersmentioning
confidence: 99%
“…One study has shown that white light interferometry-based methods are capable of measuring flow rate [83]. Here, the self-compensation fibre-optic sensor employed the principles of cantilever beam mechanics.…”
Section: Measurement Of Flow Parametersmentioning
confidence: 99%
“…sensors have been widely used in temperature, pressure and chemical measurements [36][37][38][39][40][41][42][43][44]. This kind of sensors possess a series of characteristics such as compactness, lightweight, and generally immunity to electromagnetic interference ( EMI) [1].…”
Section: Application Of Fabry-perot Sensorsmentioning
confidence: 99%
“…The Center for Photonics Technology at Virginia Tech has developed optical sensors for a wide range of analytes such as temperature [15], pressure [16,17], flow [18], acoustics [17,19], humidity, and various gases [20,21], including the world’s smallest high temperature pressure sensor [22]. The layer-by-layer electrostatic self-assembly (LbL/ESA) process allows direct attachment of these probes to the fiber surface, either the endface or side surfaces.…”
Section: Introductionmentioning
confidence: 99%